(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Context: Shilajit is a natural rock exudate used to prevent and combat problems with diabetes. It also has antioxidant, hypolipidemic and hypoglycaemic properties. Aim: To evaluate the effect of Shilajit on endothelial function in type 2 diabetes mellitus patients. Settings and Design: Randomized, double blind, placebo-controlled study. Methods and Material: After the ethics committee approval and informed consent, forty subjects were randomized to receive either Shilajit 250 mg or placebo (two capsules twice daily for 12 weeks). Endothelial function was evaluated with Reflection index (RI), Augmentation index (AIx), Subendocardial viability ratio (SEVR), Ankle Brachial Index (ABI), Pulse wave velocity(PWV) and Systemic vascular resistance (SVR) at baseline,4,8,12 weeks. Lipid profile and biomarkers Nitric oxide,MDA, Glutathione, hsCRP were evaluated at baseline and post treatment. Statistical analysis used: Data was expressed as mean ±SD. Paired and unpaired t- tests were performed for within group and between groups analysis, respectively. A p value < 0.05 was considered statistically significant. Results: After 12 weeks of treatment, Shilajit produced statistically significant increase in mean RI from baseline (-2.29±1.43 to -8.61±2.70; p<0.001) and in mean SEVR (145.5±24.89 to 150.9±24.08; p<0.05). Compared to placebo, Shilajit produced statistically significant increase in mean percentage change with RI, AIx, SEVR, and SVR, suggesting improvement in endothelial function. There was also statistically significant reduction in hsCRP, MDA, total cholesterol, LDL-C, triglycerides and increase in NO, GSH, HDL-C. The drug was well tolerated and no subjects discontinued due to adverse drug reactions. Conclusion: Shilajit showed significant improvement in endothelial function as evidenced with change in reflection index. It also improved other cardiovascular parameters and biomarker levels. Further studies are warranted in more number of subjects.